Relevansi Epistemologi Ibnu Khaldun dalam Kurikulum Pendidikan Islam Kontemporer - Afifah Nur Azizah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to examine the relevance of Ibn Khaldun’s epistemology to the development of contemporary Islamic education curricula. Amid ongoing challenges in integrating religious and secular sciences within Islamic education systems, Ibn Khaldun's conceptual framework offers an epistemological solution through the integration of revelation, reason, and experience. This research employs a qualitative approach using literature study methods. Data were obtained from a review of Ibn Khaldun’s works—particularly Muqaddimah—and recent academic literature published within the last five years. The results reveal that Ibn Khaldun proposed a staged (tadarruj), integrative, and practical model of education that unites naqliyah (revealed) and aqliyah (rational) sciences within a coherent epistemological framework. His thought is not only theoretical but also pragmatic, emphasizing the utility of knowledge in shaping civilization. Therefore, Ibn Khaldun’s epistemology is highly relevant as a foundation for constructing Islamic education curricula that are contextual, humanistic, and value-oriented. These findings reaffirm Ibn Khaldun’s position as a transformative thinker in global Islamic educational discourse.